Post-Partnership Strategies for Defining Corporate Responsibility: The Business Social Compliance Initiative - Egels-Zandén, Niklas (Journal of business ethics, 2007)
While cross-sectoral partnerships are frequently presented as a way to achieve sustainable development, some corporations that first tried using the strategy are now changing direction. Growing tired of what are, in their eyes, inefficient and unproductive cross-sectoral partnerships, firms are starting to form post-cross-sectoral partnerships (‚post-partnerships’) open exclusively to corporations. This paper examines one such post-partnership project, the Business Social Compliance Initiative (BSCI), to analyse the possibility of post-partnerships establishing stable definitions of ‚corporate responsibility’. We do this by creating a theoretical framework based on actor-network theory (ANT) and institutional theory. Using this framework, we show that post-partnerships suffer from the paradox of striving to marginalise those stakeholders whose support they need␣for establishing stable definitions of ‚corporate responsibility’. We conclude by discussing whether or not post-partnership strategies, despite this paradox, can be expected to establish stable definitions of ‚corporate responsibility’.